Studies on the genus Atriplex (Chenopodiaceae) in Italy. IX. Atriplex mollis and note on its occurrence in continental Europe - Iamonico, Duilio (Mediterranean Botany, 2024)
The typification of the name Atriplex mollis, validly published by R. L. Desfontaines in Flora Atlantica, is discussed. A specimen deposited at G (barcode G00386803) is designated as the lectotype of the name. The distribution in Europe of the species is also discussed. It was indicated for Sardinia only (Italy, Southern Europe) in a single locality (San Paolo pond, Cagliari Province). No specimen that proves the occurrence of the species in Sardinia is in extant. Moreover, the overlapping of a map published in 1912 and the current satellite images, allowed to verify that the area in which A. mollis grew up, including wetlands at the beginning of the XX century, is currently almost totally covered by buildings and commercial/industrial sites. In other words, the habitat where the species occurred was destroyed. As a consequence, at the current state of knowledge, the species is here assessed as extinct (EX) at national level according to the IUCN categories.